SARS‐CoV‐2 placentitis and severe pregnancy outcome after maternal infection: A Danish case series. (23rd March 2023) - Nielsen, Stine Y.; Hvidman, Lone E.; Aabakke, Anna J. M.; Olsen, Tina E.; Johnsen, Iben B. G.; Bogaard, Pauline W.; Petersen, Astrid; Westergaard, Hanne B.; Sørensen, Anne; Hedermann, Gitte; Rønneberg, Elisabeth T.; Thisted, Dorthe; et al.
Abstract: Introduction: SARS‐CoV‐2 infection during pregnancy may cause viral inflammation of the placenta, resulting in fetal demise even without fetal or newborn infection. The impact of timing of the infection and the mechanisms that cause fetal morbidity and mortality are not well understood. Material and methods: To describe placental pathology from women with confirmed SARS‐CoV‐2 infection during pregnancy, a SARS‐CoV‐2 immunohistochemistry‐positive placenta and late miscarriage, stillbirth, neonatal death, or medically indicated birth due to fetal distress. Results: The triad of trophoblastic necrosis, inflammatory intervillous infiltrates, and increased perivillous fibrinoid deposition was present in all 17 placentas; the pregnancies resulted in eight stillbirths, two late miscarriages (19 and 21 weeks' gestation), and seven liveborn children, two of which died shortly after delivery. The severity of maternal COVID‐19 was not reflected by the extent of the placental lesions. In only one case, SARS‐CoV‐2 was detected in lung tissue samples from the fetus. The majority events (miscarriage, stillbirth, fetal distress resulting in indicated birth, or livebirth, but neonatal death) happened shortly after maternal SARS‐CoV‐2 infection was diagnosed. Seven of eight sequenced cases were infected with the Delta (B.1.617.2) virus strain. Conclusion: We consolidate findings from previous case series describing extensive SARS‐CoV‐2 placentitis and placental insufficiency leading to fetal hypoxia. We found sparse evidence to support the notion that SARS‐CoV‐2 virus had infected the fetus or newborn. Abstract : We report 17 cases with placental pathology from women with confirmed SARS‐CoV‐2 infection during pregnancy, a SARS‐CoV‐2 immunohistochemistry‐positive placenta and late miscarriage, stillbirth, neonatal death, or medically indicated birth due to fetal distress. Our findings consolidate previous reports describing extensive SARS‐CoV‐2 placentitis and placental insufficiency leading to fetal hypoxia.